Pembuatan Aplikasi Manajemen Sumber Daya Manusia Berbasis Web pada PT. X - Faren Areita Kharisma; Lily Puspa Dewi; Silvia Rostianingsih (Jurnal Infra, 2019)
PT. X is a company engaged in the culinary sector. PT. X has 3 outlets and 1 production site. The Department of Human Resources and Development & General Affairs is centered on an outlet which is also the head office in Surabaya. Before application development begins, analysis and design are carried out with data flow diagrams and entity relation diagrams. This application is created using HTML, PHP, JavaScript, MySQL database, and Bootstrap framework languages. The application created includes features of permission requests, sickness, overtime, and leave via the web. In addition the application is made calculation of employee salaries, employee evaluation, recap. The end result of application development is the calculation of employee salaries each month and the calculation costs of PPh 21, making staff evaluation criteria and evaluating staff. As well as making report attendance reports, training reports, administrative reminder for employees who will be retired in the near future. The results of the questionnaire showed that the user's assessment of the application's appearance was 66.66% of respondents answered well and 33.33% of respondents answered very well, the user's assessment of information integration was 66.66% of respondents answered well and 33.33% of respondents answered very well, assessment users of the application feature are 100% of respondents answered well, the user's assessment of the HRD manager's features is 66.66% of respondents answered well and 33.33% of respondents answered very well, the user's assessment of the suitability of performance evaluation features is 100% of respondents answered well, users towards the program report is 100% of respondents answered well, the user's assessment of the application speed is 66.66% of respondents answered well and 3.33% of respondents answered very well, the user's assessment of the ease of use of the application was 66.66% of respondents answered well and 33, 33% of respondents answered very well, the user's assessment of conformity with the problem was 33, 33% of respondents answered enough and 66.66% of respondents answered well, the user's assessment of the overall application was 33.33% of respondents answered well and 66.66% of respondents answered very well.